2002
DOI: 10.1111/1467-8624.00472
|View full text |Cite
|
Sign up to set email alerts
|

Some Ways in Which Neighborhoods, Nuclear Families, Friendship Groups, and Schools Jointly Affect Changes in Early Adolescent Development

Abstract: This study assessed some ways in which schools, neighborhoods, nuclear families, and friendship groups jointly contribute to positive change during early adolescence. For each context, existing theory was used to develop a multiattribute index that should promote successful development. Descriptive analyses showed that the four resulting context indices were only modestly intercorrelated at the individual student level (N = 12,398), but clustered more tightly at the school and neighborhood levels (N = 23 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
193
2
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(212 citation statements)
references
References 44 publications
11
193
2
6
Order By: Relevance
“…While HFASD children in mixed dyads "looked better" and were not significantly different from other HFASD children with respect to the aspects of cognitive social, and emotional functioning that we assessed, the possibility remains that the HFASD children still differed in some systematic way. For example studies of typically and atypically developing children have found that personality (Fordham and Stevenson-Hinde 1999;Shiner and Caspi 2003), self-esteem (Azmitia 2001), aspects of executive functioning and attention (Hay et al 2004), levels of co-morbid psychopathology (Deater-Deckard 2001;Hay et al 2004), and emotion regulation (Eisenberg et al 2000), as well as parent characteristics including levels of social support and networks (Cook et al 2002;Bost 1995;Melson et al 1993) also play a role in children's abilities to form friendships.…”
Section: Discussionmentioning
confidence: 99%
“…While HFASD children in mixed dyads "looked better" and were not significantly different from other HFASD children with respect to the aspects of cognitive social, and emotional functioning that we assessed, the possibility remains that the HFASD children still differed in some systematic way. For example studies of typically and atypically developing children have found that personality (Fordham and Stevenson-Hinde 1999;Shiner and Caspi 2003), self-esteem (Azmitia 2001), aspects of executive functioning and attention (Hay et al 2004), levels of co-morbid psychopathology (Deater-Deckard 2001;Hay et al 2004), and emotion regulation (Eisenberg et al 2000), as well as parent characteristics including levels of social support and networks (Cook et al 2002;Bost 1995;Melson et al 1993) also play a role in children's abilities to form friendships.…”
Section: Discussionmentioning
confidence: 99%
“…Rankin and Quane (2002) also reported a cross-context moderator effect, between the neighborhood context and the family context; and Crosnoe et al (2002) reported cross-context moderator effects between protective factors in the family context and in the school context and a single risk factor of models for deviance in the peer context. However, when Cook et al (2002) examined interactions of measures across four social contexts-school, neighborhood, friendship group, and family-no cross-context interactions were found. Because their measures were of the overall "quality" of each of the four contexts rather than of both protective factors and risk factors within each context, interaction effects would be unlikely to emerge.…”
mentioning
confidence: 87%
“…The current preoccupation with context was, of course, presaged long ago by Kurt Lewin (1951) and more recently by Urie Bronfenbrenner (1986), as well as by others. Cronbach (1982), for example, argued that "Understanding an adolescent's experience … seems to require a community-wide ecological perspective" (p. 74) and that perspective has animated a wide array of contemporary studies (e.g., Arthur, Hawkins, Pollard, Catalano, & Baglioni, 2002;Beam, Gil-Rivas, Greenberger, & Chen, 2002;Cook, Herman, Phillips, & Settersten, 2002;Crosnoe, Erickson, & Dornbusch, 2002;Eccles, Early, Frasier, Belansky, & McCarthy, 1997;Elder & Conger, 2000;Elliott et al, 2005;Furstenberg, Cook, Eccles, Elder, & Sameroff, 1999;Herrenkohl et al, 2000;Novak & Clayton, 2001). Such studies have encompassed various domains of the social environment including the family, the peer group, the school, and the neighborhood; and they have investigated a wide range of adolescent experience including depression, academic achievement, delinquency, and substance use.…”
mentioning
confidence: 99%
“…In the life-course perspective, groups of individuals who populate a person's social contexts are seen as configurations of people with whom individuals travel over their lives and who positively or negatively affect their transitions and pathways (Kahn and Antonucci 1980;Hagestad 2002). For example, a study of the effects of social contexts on adolescents' lives by Cook and associates found that schools, neighbourhoods, peers, and families had independent and additive influences on adolescent school success (Cook et al 2002).…”
Section: Introductionmentioning
confidence: 99%